Survival in the Sahel: An Ecological and Developmental Challenge - Leisinger, Klaus M.; Schmitt, Karin (International Service for National Agricultural Research, 1995)
Survival in the Sahel revisits the baffling puzzle of the development problems of the Sahel. Using practical examples and sound data, it shows how past development strategies contributed to the region's deteriorating socioeconomic and environmental conditions. It also shares some of the success stories of the last two decades, recommending new development approaches, and presenting some alternative ways to deal with the present Sahelian situation. The book is divided into two parts. Part I discusses the Sahel, its geography, history, environment, and socioeconomics. Part II highlights the case of Mali as a typical Sahelian country. These sections raise a number of implications. First, global solidarity among aid organizations is a prerequisite to solving the problems of the Sahel. Second, new development strategies have a better chance of success if they have a long-term perspective, are based on small-scale actions, use a more integrated approach, take more account of women, and seek the full participation of local people. Third, the contribution of agricultural research to solving the problems of the Sahel, its people, and its natural environment cannot be ignored. Fourth, even organizations that do not have development assistance as their main raison d'etre can and should be involved in the development of the Sahel